A STUDY OF COLLEGE ENGLISH MAJORS’ CRITICAL THINKING COMPETENCE IN USING INTERNET RESOURCES - Wang, Jin-ba (Proceedings of National Aviation University (archive), 2019)
Since online information can be written by anyone and there is no quality control for them, it becomes our responsibility, as individuals, to judge what is right, wrong, immoral, illegal, biased or totally incorrect. This decision-making process is called critical thinking. The study involved 105 English students from a university in north China and aimed to investigate what kinds of critical thought processes were engaged when accessing and using online information. The results showed that there was a need for English majors to be more critical when using online information. Hence educators and learning institutions need to address this matter and guide the students properly in using the online information.